Dietary vitamin C and E modulates oxidative stress induced-kidney and lens injury in diabetic aged male rats through modulating glucose homeostasis and antioxidant systems - Ozkaya, Dilek; Naziroglu, Mustafa; Armagan, Abdullah; Demirel, Alpay; Koroglu, Banu Kale; Colakoglu, Neriman; Soenmez, Tolga Taha (Wiley, 2011)
Diabetes induces oxidative stress in aged human and rat, although daily supplementation of vitamins C and E (VCE) can be beneficial to aged diabetic rats by reducing free radical production. The aim of the present study was to evaluate whether dietary VCE supplementation relieves oxidative stress in streptozotocin (STZ)-induced diabetic in aged rats. Thirty aged rats were randomly divided into three groups. The first group was used as a control. The second group was made diabetic using a single dose of intraperitoneal STZ. VCE-supplemented feed was given to aged diabetic rats constituting the third group. On the 21st day of the experiment, blood, lens and kidney samples were taken from all animals. Glutathione peroxidase (GSH-Px) activity in lens and kidney, reduced glutathione (GSH), vitamin E and beta-carotene concentrations in kidney were lower in the diabetic group than in the control whereas plasma glucose, urea and creatinine, and kidney and lens peroxidation (LP) levels were higher in the diabetic group than in the control. However, kidney and lens LP levels, and plasma glucose, urea and creatinine values were decreased by VCE supplementation. Lens and kidney GSH-Px activity, kidney GSH, vitamin E and beta-carotene concentrations and erythrocyte counts were increased by VCE treatment. Kidney weights, vitamin A, haemoglobin, hematocrit, leukocyte and platelets values were not changed by diabetes and/or VCE supplementation. VCE ameliorated also diabetes-induced histopathological changes in kidney. In conclusion, we observed that VCE supplementation is beneficial towards kidney and lens of aged diabetic rats by modulating oxidative and antioxidant systems. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: diabetes; aged; kidney; lens; vitamin C and E; oxidative stress; hematological values